Demographic and Clinical Determinants of Tuberculosis and TB Recurrence: A Double-Edged Retrospective Study from Pakistan. (28th November 2022) - Mujtaba, Mariam Ahmed; Richardson, Matthew; Shahzad, Hira; Javed, Muhammad Ishaq; Raja, Ghazala Kaukab; Shaiq, Pakeeza Arzoo; Haldar, Pranabashis; Saeed, Sadia
Abstract : Objective . TB recurrence is the second episode of TB after initial treatment bringing about an additional 7% load in TB burden intensified by 17.7% of multidrug-resistant recurrent cases. It is necessary to curb recurrence so that attempts to deal with active disease can be made more effective. This study aimed to characterize sociodemographic and clinical factors associated with recurrent TB in a high-burden setting. Methodology . A retrospective case-control study was carried out at two hospitals in Rawalpindi, Pakistan. TB patients and controls were included in the study. Sociodemographic and clinical data were collected by questionnaire from all subjects. Multivariate regression analysis was performed to determine factors associated with TB and TB recurrence respectively. Results . In our study cohort, factors significantly associated with TB were low BMI (OR: 0.961 (CI 0.954–0.968), p < 0.001 ), female gender (OR: 2.065 (CI 1.922–2.219), p < 0.001 ), being single/unmarried (OR: 1.214 (CI 1.109–1.328), p = 0.003 ), middle-income status (OR: 1.935 (CI 1.616–2.323), p < 0.001 ), smoking (OR: 1.567 (CI 1.435–1.710), p < 0.001 ), and diabetes mellitus (OR: 1.142 (CI 1.017–1.278), p = 0.023 ). TB recurrence constituted 11.2% of patients presenting to the hospital. Compared with the first episode of TB, cases with recurrence were more likely to be older (OR: 1.011 (CI 1.004–1.017), p < 0.001 ), have disease awareness (OR: 1.906 (CI 1.486–2.437), p < 0.001 ), smear positive (OR: 2.384 (CI 1.650–3.536), p < 0.001 ), and be drug-resistant (OR: 5.615 (CI 4.265–7.386), p < 0.001 ). Conclusion . In the present study cohort, low BMI, female gender, being single, middle-income status, being unemployed, smoking, and being diabetic came out to be the sociodemographic and clinical risk factors for TB. Further exploring the TB cases increasing age, drug resistance and smear positivity stood out to be the major sociodemographic and clinical factors of TB recurrence despite high disease awareness.